2005
DOI: 10.1536/ihj.46.1007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Plasma Levels of Brain Natriuretic Peptide and Left Ventricular Ejection Fraction in Asymptomatic Patients With Previous Myocardial Infarction

Abstract: SUMMARYWhile the usefulness of measuring the plasma levels of brain natriuretic peptide (BNP) in cases with worsening heart failure and severe heart failure has already been established, the benefits of evaluation of this parameter in asymptomatic stable patients with left ventricular dysfunction is still under debate. Left ventricular function was evaluated in 141 ambulatory outpatients with a previous history of myocardial infarction not associated with symptoms of heart failure for at least one year. The pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…A study by Watanabe, et al revealed no correlation between BNP levels and normal ejection fraction after myocardial infarction. 15) In the present study, we found no such correlation. However, as already pointed out, all of our patients had normal systolic function, which we considered to be the reason for not finding such a correlation.…”
Section: Discussioncontrasting
confidence: 74%
“…A study by Watanabe, et al revealed no correlation between BNP levels and normal ejection fraction after myocardial infarction. 15) In the present study, we found no such correlation. However, as already pointed out, all of our patients had normal systolic function, which we considered to be the reason for not finding such a correlation.…”
Section: Discussioncontrasting
confidence: 74%
“…On the other hand, it is reasonable to assess BNP in asymptomatic patients with a previous history of myocardial infarction and a low ejection fraction. 20) The data obtained in the present study confirm that plasma levels of BNP are elevated in the early stages of AMI, peaking after 24 hours from the onset of symptoms. A worsened prognosis related to the second BNP measurement for the short-term may have important practical implications.…”
Section: Discussionsupporting
confidence: 85%
“…Afterwards, BNP rises as a result of systolic and diastolic dysfunction and increased wall stress of the left ventricle 35. There have been several evidences, supporting that variation in plasma BNP level during acute phase of AMI, can be used as a prognostic factor 1.…”
Section: Introductionmentioning
confidence: 99%